La notion d'« acte collectif » dans le sacrifice humain grec - Bonnechere, Pierre (Phoenix: Journal of the Classical Association of Canada = Revue de la Société Canadienne des Études Classiques, 1998)
As a collective act, human sacrifice in Greece has all the trappings of animal sacrifice. Being contrary to the norms of Greek society, it derives its inversive nature solely from the context in which it is performed. If we leave aside myths in which an entire community is threatened with extinction, ancient writers played upon the elements of perversity inherent in the act. Thus in tragedy, the community only has recourse to human sacrifice when it is not funtioning normally. Among foreign peoples, on the other hand, the community practises human sacrifice without due cause. Being the polar opposite of the Greek community, the norm is for its sacrificial victims to be human; it differs from the world of the Greek tragic city in that its abnormality is permanent rather than temporary, and is set out for all to see./En tant qu'acte collectif, le sacrifice humain grec présente les apparences de l'immolation animale: anti-valeur de la société hellénique, son caractère inversif lui vient donc seulement du contexte dans lequel il est perpétré. À côté des cas légendaires de danger d'éradication totale de la communauté, les auteurs anciens se sont plu toutefois à jouer sur les possibilités déviantes inhérentes à l'acte. Ainsi dans la tragédie, le collectivité qui recourt à des sacrifices humains est toujours bancale. Chez les étrangers, la communauté qui sacrifie le fait sans mobile; aux antipodes de la collectivité grecque, la victime de tous les jours y est humaine; la différence avec le monde tragique réside en ce que la déviance, permanente, y est exposée au grand jour.